Cardiovascular Abnormalities and Gene Mutations in Children With Noonan Syndrome - Sun, Ling; Xie, Yu-mei; Wang, Shu-shui; Zhang, Zhi-wei (Frontiers in Genetics, 2022)
Background: Common cardiac abnormalities in Noonan syndrome (NS) include congenital heart diseases (CHD), pulmonary valve stenosis and hypertrophic cardiomyopathy (HCM). Molecular diagnoses are enabling earlier and more precise diagnosis of patients who have a subtle or atypical presentation. The aims of this study were to investigate genotype-phenotype associations with respect to Noonan syndrome (NS)-associated cardiac abnormalities and catheter or surgery-based interventions conditions. Methods: From January 2019 to December 2021, 22 children with a confirmed molecular diagnosis of NS combined with cardiovascular abnormalities were consecutively enrolled into the current study. A comprehensive review was carried out of echocardiography and electrocardiogram results, second-generation whole-exome sequencing results and catheter or surgery-based interventions conditions. Results: The main manifestations of electrocardiogram abnormalities were QTc prolongation, abnormal Q wave in the precordial lead and limb lead, right ventricular hypertrophy and left or right deviation of the electrical axis. The most commonly detected abnormality was pulmonary valve dysplasia with stenosis, seen in 15 (68.2%) patients, followed by atrial septal defect in 11 (50%) patients. Seven genes (RAF1, RIT1, SOS1, PTPN11, BRAF, SOS2, and LZTR1) were found to contain disease-associated variants. The most commonly observed genetic mutations were PTPN11 (27%) and RAF1 (27%). Each genotype was associated with specific phenotypic findings. RIT1, SOS1, PTPN11, and SOS2 had common echocardiography features characterized by pulmonary valve stenosis, while RAF1 was characterized by HCM. Interestingly, patients with BRAF mutations were not only characterized by HCM, but also by pulmonary valve stenosis. In the cohort there was only one patient carrying a LZTR1 mutation characterized by left ventricle globose dilation. Ten cases underwent catheter or surgery-based interventions. All the operations had immediate results and high success rates. However, some of the cases had adverse outcomes during extended follow-up. Based on the genotype-phenotype associations observed during follow-up, BRAF and RAF1 genotypes seem to be poor prognostic factors, and multiple interventions may be required for NS patients with severe pulmonary stenosis or myectomy for HCM. Conclusions: The identification of causal genes in NS patients has enabled the evaluation of genotype-cardiac phenotype relationships and prognosis of the disease. This may be beneficial for the development of therapeutic approaches.